The role of self-advocacy and self-determination in positive adjustment for autistic adolescents and young adults: a mini-review - Martino, Daniele C.; Brantley, Alexa; Scarpa, Angela (Frontiers in Child and Adolescent Psychiatry, 2025)
Autistic individuals have an increased likelihood for negative adjustment relative to their peers, often as a result of adverse experiences. Consistent with the biosocial model of resilience and the growing neurodiversity movement, identifying factors that may contribute to positive outcomes among autistic individuals is an urgent research priority. The present review explores the existing literature on the role of self-advocacy and self-determination in promoting positive adjustment for autistic adolescents and young adults. Findings point to encouraging associations of self-advocacy and self-determination with various adjustment outcomes, including educational and employment outcomes, socialization, relationship development, identity development, self-concept, and quality of life. Implications are discussed, including limitations, directions for future research, and considerations for designing interventions that support autistic individuals to act with the agency and autonomy they desire.